2014
DOI: 10.1186/1756-3305-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Glossina palpalis palpalis populations from Equatorial Guinea belong to distinct allopatric clades

Abstract: BackgroundLuba is one of the four historical foci of Human African Trypanosomiasis (HAT) on Bioko Island, in Equatorial Guinea. Although no human cases have been detected since 1995, T. b. gambiense was recently observed in the vector Glossina palpalis palpalis. The existence of cryptic species within this vector taxon has been previously suggested, although no data are available regarding the evolutionary history of tsetse flies populations in Bioko.MethodsA phylogenetic analysis of 60 G. p. palpalis from Lub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…However, the isolation of Bioko Island may be a remnant of range fragmentation of mangroves, at least if we assume that mangrove forests were ubiquitous in this region during glacial times. This is for example the case for the insect Glossina palpalis palpalis , where Bioko populations have been isolated, resulting in a unique clade, different from mainland populations [ 58 ]. Therefore, future studies should consider mangrove samples from Bioko to assess the full impact of the IBC corridor on genetic connectivity and potential range fragmentation of Central African mangrove populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the isolation of Bioko Island may be a remnant of range fragmentation of mangroves, at least if we assume that mangrove forests were ubiquitous in this region during glacial times. This is for example the case for the insect Glossina palpalis palpalis , where Bioko populations have been isolated, resulting in a unique clade, different from mainland populations [ 58 ]. Therefore, future studies should consider mangrove samples from Bioko to assess the full impact of the IBC corridor on genetic connectivity and potential range fragmentation of Central African mangrove populations.…”
Section: Discussionmentioning
confidence: 99%
“…40 km from the edge of the continental shelf at less than 60 m below sea level [ 56 , 57 ]. It was repeatedly connected to mainland Cameroon during glacial times [ 56 58 ]. Following glacial retreat ca .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that tsetse populations are genetically structured [ 21 , 22 ]. Especially G. p. palpalis, clustering has been observed with distinct West African and Central African clades [ 8 , 15 , 23 , 24 ], however, very few of such data are available on tsetse populations in Nigeria [ 15 , 17 , 18 , 25 , 26 ], where these two clades could meet as the country links West and Central Africa.…”
Section: Introductionmentioning
confidence: 99%
“…palpalis , the very high bootstrap values observed between Central and West Africa and between Cameroon and RDC subsamples suggest subspeciation, if not more, in the ecological sense of it (adaptively divergent but not necessarily sexually isolated entities, see [ 40 , 54 ]). The existence of three subspecies (or even species) separating flies from West Africa (Ivory Coast), South of Cameroon, Equatorial Guinea and DRC has already been suggested, based on mtDNA (COI) [ 13 ] and there are probably more than that [ 55 ]. Here, our seven microsatellite loci provide a strong confirmation that G .…”
Section: Discussionmentioning
confidence: 99%